A qualitative exploration of the future of nutrition and dietetics in Australia and New Zealand: Implications for the workforce. Issue 4 (30th March 2022) - Boak, Rachel; Palermo, Claire; Beck, Eleanor J.; Patch, Craig; Pelly, Fiona; Wall, Clare; Gallegos, Danielle
Abstract: Aim: We aimed to explore the future roles of nutrition and dietetics professionals, and what capabilities the workforce would need to fulfil these roles. Method: A qualitative interpretive approach was employed. We conducted individual interviews with nutrition and non‐nutrition thought leaders external to the profession. In addition, we conducted focus groups with experts within the nutrition and dietetics profession, academic dietetics educators and students/recent nutrition and dietetics graduates (total sample n = 68). Key nutrition‐related issues and challenges, drivers for change and potential future roles of the profession were explored. Data were analysed using a team‐based thematic analysis approach. Results: Future roles of nutrition and dietetics professionals were described as food aficionados, diet optimisers, knowledge translators, equity champions, systems navigators and food systems activists, change makers, activists and disruptors. In addition, science was identified as a uniting framework underpinning the professions. An additional 16 critical capabilities were considered to underpin practice. Conclusion: The results demonstrated that the current and future needs for workforce education and development need to address the impact of climate change, growing inequities, the democratisation of knowledge and the disruption of health and food systems. Education providers, regulators, professional associations and citizens need to work together to realise roles that will deliver on better health for all.